Putting Large‐Scale Infrastructure Projects First: The COVID‐19 Pandemic in Indigenous Mexico. (27th December 2020) - Hofmann, Susanne
Abstract : This article argues that whilst indigenous people are central to the Mexican president's official developmentalist discourse of bringing prosperity to the country's marginalised and poor, their needs during the COVID‐19 pandemic have not been met and their interests have been sidelined. Whilst experiencing serious loss of trading revenue, negative impacts of misinformation, and lack of access to appropriate healthcare, indigenous Mexicans also faced the aggressive advance on their territories of large‐scale infrastructure projects, which have become the backbone of the president's strategy for countering the economic recession caused by the pandemic. The discontinuation of relevant legal means to challenge the advance of the megaprojects during the pandemic effectively threatened indigenous people's democratic rights to protect their land, identities and way of life.